Understanding the harm of rape - Kelland, Lindsay-Ann (Rhodes University, Faculty of Humanities, Department of Philosophy)
The aims of this thesis are twofold: to provide an account of the lived experience of the harm of male-on-female rape in patriarchal societies and, on the basis of this account, to generate suggestions that could be of use in the recovery process for survivors of this type of rape. In order to reach these aims my thesis is divided into three parts. In the first part, I propose a phenomenologically based account of women's situation as a group under patriarchy, according to which women as a group are subjugated to the hegemonic rule of patriarchal ideology. I argue, further, that the meaning, place and pervasiveness of sexual objectification in the lives of women under patriarchy typically results in women's alienation from their bodies and creates an atmosphere of threat under which women qua women are especially vulnerable to rape. In the second part, I explore the lived experience of the harm of rape; focusing, first, on the reflexive process whereby a survivor attempts to understand how she has been harmed and, second, on providing explanations based on shared features in the lives of women for two phenomena reported to be experienced by rape victims in the aftermath of the trauma, which I call 'shattering' and 'fragmentation'. My discussion of the lived experience of the harm of rape is meant to supplement existing accounts in the contemporary literature that, I argue, are limited to a thirdperson, objective point of view and so fail to provide a link between the harms they describe and the victim's actual experience of these harms. Finally, I defend two suggestions for the building up of the survivor's agency and personhood in the aftermath of rape"”the deliberate therapeutic use of feminist consciousness-raising and the use of narrative understanding.,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Rape -- Social aspects -- Research -- South Africa; Rape -- Psychological aspects -- Research -- South Africa; Rape trauma syndrome -- Research -- South Africa; Rape victims -- South Africa; Patriarchy -- South Africa; Sexual dominance and submission -- South Africa